Architecturally Inspired Furniture: Creating Furniture Inspired By Masterpieces In Architecture.: APPLICATION IN ADVANCED FURNITURE COURSE - Magdy Ibrahim, Sadeka Shakour (International Journal of Advanced Science and Technology, 2019)
Architecture is one of humanity’s most visible and long-lasting forms of expression, spanning the entire length of humanity. Most historic civilizations are even identified by their surviving architectural relics: The Pyramids of Giza in Egypt, The Golden Pavilion in Japan, or The Taj Mahal in India. Here, the research focuses on a few of the icons of modern architecture, utilizing masterpiece examples of masters of architecture that are true masters of their craft. We employ some of the icons of modern architecture as key elements for analyzing, developing, and evaluating the advanced furniture design we will work on. This research explores the possibility of producing a line of furniture design inspired by the icons of modern architecture, masterpieces of architectural design by famous pioneers in the classroom environment. Borrowing the architectural language to produce furniture is an experimental technique which expects to find inspiration from other designers work. In the advanced furniture design course, which is offered as an elective in the interior design program, the students were asked to produce original designs of furniture pieces that reflect the design language of a particular building of a famous architect. The goal is for the students to be able to analyze the style elements, find the defining lines, and eventually producing their own designs based on their finding. The exercise as successful as it was did not finish as desired, producing physical furniture pieces, but only settled for scale models which the students were able to produce in the allocated time and resources. This research would like to expand that opportunity to detail and build some of the resultant ideas in order to close the design process circle by producing the expected final product.